Human Growth Factor/Immunoglobulin Complexes for Treatment of Myocardial Ischemia-Reperfusion Injury - Liebman, Benjamin; Schwaegler, Claire; Foote, Andrea T.; Rao, Krithika S.; Marquis, Taylor; Aronshtam, Alexander; Bell, Stephen P.; Gogo, Prospero; LaChapelle, Richard R.; Spees, Jeffrey L. (Frontiers in Bioengineering and Biotechnology, 2022)
Hepatocyte Growth Factor (HGF) and Fibroblast Growth Factor 2 (FGF2) are receptor tyrosine kinase agonists that promote cell survival after tissue injury and angiogenesis, cell proliferation and migration during tissue repair and regeneration. Both ligands have potential as systemic treatments for ischemia-reperfusion injury, however clinical use of HGF and FGF2 has been limited by poor pharmacokinetic profiles, i.e., their susceptibility to serum proteases, rapid clearance and short half-lives. Previously, we reported vaso- and cardioprotective protein complexes formed between HGF and polyclonal, non-specific immunoglobulin (IgG) with therapeutic efficacy in a rat model of myocardial ischemia with reperfusion (MI/R). Here, using a pre-clinical porcine MI/R model, we demonstrate human HGF/IgG complexes provide significant myocardial salvage, reduce infarct size, and are detectable in myocardial tissue 24 h after intracoronary injection. Furthermore, we show that multiple daily infusions of HGF/IgG complexes after MI do not lead to production of HGF-specific auto-antibodies, an important concern for administered biologic drugs. In experiments to identify other growth factors that non-covalently interact with IgG, we found that human FGF2 associates with IgG. Similar to human HGF/IgG complexes, FGF2/IgG complexes protected primary human cardiac endothelial cells under simulated ischemia (1% oxygen and nutrient deprivation) for 48–72 h. Molecular modeling studies suggested that FGF2 and HGF both interact with the Fc domain of IgG. Also, we tested whether an Fc-fusion protein would bind FGF2 to form complexes. By native gel electrophoretic assays and biochemical pulldowns, we found that Jagged1, a Notch1 ligand that controls stem cell self-renewal and tissue regeneration, bound FGF2 when presented as a Jagged1- Fc fusion protein. Our results suggest that human growth factor/IgG and FGF2/Fc- fusion complexes have potential to provide a biologics platform to treat myocardial ischemia-reperfusion and other forms of tissue injury.